Простые последовательности ДНК в геномах эукариот - Ермак, Г.З.; Картель, Н.А. (Биополимеры и клетка, 1989)
Кратко рассмотрены распространение простых последовательностей ДНК з геномах различных организмов, их локализация, возможные функции, происхождение и эволюция. Обсуждена возможность участия этих последовательностей в регуляции работы генов и рекомбинациях. Коротко розглянуто поширення простих послідовностей ДНК у геномах різних організмів, їхня локалізація, можливі функції, походження і еволюція. Обговорено можливість участі цих послідовностей у регуляції роботи генів і рекомбінаціях. Spreading of simple DNA sequences in genomes of different organisms as well as their localization, possible functions, origin and evolution are briefly considered. Those sequences are discussed for the possibility to participate in regulation of gene activity and recombinations. Probable mechanisms of simple sequences formation are shown. A conclusion is made that these sequences are not «selfish DNA» but are active and progressive elements.